A Consensus Meeting on Expert Recommendations on Operating Specifications for Laparoscopic Radical Resection of Hilar Cholangiocarcinoma - Xiong, Yongfu; Jingdong, Li; Zhaohui, Tang; Lau, Joseph (Frontiers in Surgery, 2021)
Background: With advances in techniques and technologies, laparoscopic radical resection of hilar cholangiocarcinoma (HCCA) has gradually been carried out in major medical centers in China. Its feasibility and safety have been accepted by a group of Chinese surgical experts. Methods: To standardize perioperative management of HCCA by using laparoscopic resectional approach, to ensure safety of the patient with standardized management, improve prognosis of the patient, and enable proper application and refinement of this surgical approach, the expert group on specifications for laparoscopic radical resection of HCCA in China organized a consensus meeting. Results: Laparoscopic radical resection of HCCA is difficult and associated with high risks. Appropriate patients should be carefully selected and this surgical approach should be promoted gradually. The experts met and arrived at 16 recommendations on perioperative management of HCCA by using laparoscopic surgery. There were three recommendations on preoperative diagnosis and evaluation; one recommendation on surgical principles of treatment; one recommendation on indications and contraindications; one recommendation on credentialing, staffing, and equipment; nine recommendations on laparoscopic techniques in different stages of operation; and one recommendation on indications for conversion to open surgery. Conclusion: Laparoscopic surgery for HCCA is still in the early phase of development. This consensus provides a clinical reference with the aim to promote and to facilitate its further development.